FEEDING AND REPRODUCTIVE CYCLES OF THE FISH MYSTUS GULIO IN THE COOUM BACKWATERS, MADRAS - Pandian, T J (Indian Journal of Fisheries, 2011)
THIS paper reports on the feeding and reproductive cycles of Mystus gulioin the Cooum backwaters. It is based on the author's previous work concerningthe feeding habits of Megalops cypritioides collected from the samearea and during the same period.^ These two species are the most abundantcarnivorous fishes in the Cooum backwaters in the vicinity of the UniversityBuildings. A study of their feeding habits may be expected to throwsome Ught on the population dynamics of their food organisms too. It mayalso be interesting to compare the feeding and breeding habits of M. gulio inthe Cooum backwaters, with those reported for the same fish in the Hooghlyestuary (Pantulu, 1961).